2020
DOI: 10.1037/xlm0000720
|View full text |Cite
|
Sign up to set email alerts
|

Measuring task set preparation versus mind wandering using pupillometry.

Abstract: We investigated participants’ task set preparation by measuring changes in pupil diameter during a blank interval as they prepared for an easy (i.e., prosaccade) or difficult (i.e., antisaccade) trial. We used occasional thought probes to gauge “on-task” thoughts versus mind wandering. In both studies, participants’ pupil diameters were larger when anticipating an antisaccade, relative to a prosaccade, trial. In contrast, their self-reported mind wandering depended upon whether the thought probes occurred afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(64 citation statements)
references
References 68 publications
8
53
3
Order By: Relevance
“…The Schubert et al (2020) findings thus indicate that TUT reports can be somewhat reactive to errors, affecting mean TUT rates, but they don't convincingly demonstrate that mind wandering's associations with other constructs reflect performance reactivity. 2 2 Although Hutchison et al (2020) also appear to have detected performance reactivity in their pupillometry study, the findings are not straightforward.…”
Section: Reactivity To Performancementioning
confidence: 95%
See 1 more Smart Citation
“…The Schubert et al (2020) findings thus indicate that TUT reports can be somewhat reactive to errors, affecting mean TUT rates, but they don't convincingly demonstrate that mind wandering's associations with other constructs reflect performance reactivity. 2 2 Although Hutchison et al (2020) also appear to have detected performance reactivity in their pupillometry study, the findings are not straightforward.…”
Section: Reactivity To Performancementioning
confidence: 95%
“…However, if antisaccade errors artificially increased TUT reports, then Study 2 should have reduced TUT rates; in fact, TUT rates on antisaccade trials increased slightly, from .41 in Study 1 to .43 in Study 2 (proaccade TUT rates increased from .38 to .48). It is unclear, then, whether the Hutchison et al (2020) findings suggest error reactivity.…”
Section: Reactivity To Performancementioning
confidence: 99%
“…However, when probes offered only two response options (on-task vs TUT), TUT rates were higher than with 2 Although Hutchison et al (2020) also appear to have detected performance reactivity in their pupillometry study, the findings are not straightforward. Their Study 1 cued subjects on each trial to expect a prosaccade trial (a target appearing in the same location as a cue) or an antisaccade trial (a target appearing in the opposite location as a cue) 500-8000 ms later; probes appeared after target-identification responses.…”
Section: Biases From Thought-probe Framingmentioning
confidence: 91%
“…In particular, research suggests that during a lapse of attention, there is a temporary reduction in intensity. For example, as shown in Figure 1, using pupillary responses to track intensity and thought probes to track consistency, we found that when participants reported being off task (in a sustained-attention task), they exhibited much smaller pupillary responses both when waiting for a target to appear (preparatory control) and at target onset, compared with when they reported being fully on task ; see also Hutchison et al, 2020). Similar withinparticipant relations have been demonstrated in longterm memory tasks (Miller & Unsworth, 2021).…”
Section: Similarities and Differences Between Intensity And Consistency Of Attentionmentioning
confidence: 78%
“…Recently, we have utilized pupillometry, as research has suggested that the pupil dilates in response to the cognitive demands of a task and that pupil dilation is a reliable and valid indicator of intensity (attentional effort; Beatty & Lucero-Wagoner, 2000;Just & Carpenter, 1993;Kahneman, 1973). Recent research has also used fluctuation in pupillary responses as an indicator of the consistency of attention (Hutchison et al, 2020;Unsworth & Robison, 2017a). In addition, consistency can be measured using thought-probe techniques, in which participants are periodically presented with a thought probe asking if their attention is currently on task or off task (i.e., if they are mind wandering, externally distracted, or mind blanking; see Unsworth, Robison, & Miller, 2020, for a review).…”
Section: Similarities and Differences Between Intensity And Consistency Of Attentionmentioning
confidence: 99%